Cascaded Vector Control with Field-Oriented Control for Ac Induction Motor Position Servo - Bayu Adji Nur Sudarisman; Adha Imam Cahyadi; Oyas Wahyunggoro (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Precise position control of AC induction motors is essential in various industrial applications, including robotics, machine tools, and automated manufacturing systems. The main challenges arise from the nonlinear dynamics of induction motors and the lack of inherent position feedback. This study proposes a three-tier cascaded control architecture integrating a PD position controller, a PI speed controller, and a Field-Oriented Control (FOC) current loop, with a 1:10:100 bandwidth hierarchy among the loops. This design ensures effective dynamic decoupling and global asymptotic stability, verified through Lyapunov-based analysis, including robustness against rotor parameter uncertainties up to ±20%. Numerical simulations on a 1.5 kW induction motor demonstrate a rise time of 0.157 s, settling time of 0.267 s, overshoot of 9.8%, steady-state position error of 0.0008 rad, and disturbance rejection of a 2 N·m load in 95 ms. FOC implementation maintains rotor flux within ±0.1% and peak efficiency of 91% at rated torque. These results confirm that the proposed cascaded three-tier FOC architecture achieves fast, accurate, and stable position control suitable for industrial servo applications and can be extended to other AC motor types with parameter adjustment and flux control strategies.